Criação de roteiros turísticos para o Geoparque Aspirante Seridó (RN, NE do Brasil), na ótica do processo participativo - Silva, Nayara Cristina Santana da (2021)
The purpose of this study is to develop itineraries for the Seridó Aspiring Geopark, in the State of Rio Grande do Norte, Northeastern Brazil, to promote the development of sustainable tourism in the territory, seeking to analyze the involvement of different actors in the participatory process of creation. especially tour guides, travel agencies and local drivers, actors who work and sell services related to the subject of this research. The search for the construction of regional development through tourism involves the elaboration of numerous steps that together result in the promotion of tourist activity. The elaboration of tourist itineraries, one of these steps, meets the needs of visitors and presents the locality's regional identity, resulting in the stimulus to the regionalization of tourism, where the territory is analyzed as a social transformer, and not just identified as a territorial space. Regarding the methodological procedures, this was an exploratory study with a qualitative approach. Questionnaires were applied and interviews were conducted with actors who exercise roles in the elaboration and marketing of tourist itineraries for the territory of the Seridó Aspiring Geopark and with representatives of the community of the geopark territory, in addition to the use of literature review and research in scientific articles, dissertations, theses and books on the topic. This resulted in the development of three itineraries, covering the entire territory of the Seridó Aspiring Geopark, subdivided by regions that facilitate logistical aspects and at the same time can be worked on in an integrated manner: North Seridó Route, Central Seridó Route and Seridó Route South, with goals achieved in terms of valuing the region's environmental, cultural, and social aspects and generating sustainable development, considering the opinion of local communities. It is expected that the creation of these tourist itineraries will provide a better social inclusion of the community in tourist activities, encourage community empowerment, and strengthen tourist activity, considering the existing cultural diversity and the possibility of increasing local revenue in a sustainable way.